Frequent immune response to a melanocyte specific protein KU-MEL-1 in patients with Vogt-Koyanagi-Harada disease. Issue 6 (15th February 2006) - Otani, S; Sakurai, T; Yamamoto, K; Fujita, T; Matsuzaki, Y; Goto, Y; Ando, Y; Suzuki, S; Usui, M; Takeuchi, M; Kawakami, Y
Abstract : Aim: To isolate autoantigens possibly involved in the pathogenesis of Vogt-Koyanagi-Harada (VKH) disease. Methods: Autoantigens recognised by immunoglobulin G antibodies (IgG Ab) in sera from VKH patients were isolated by screening the lambda phage cDNA libraries made from melanocytes and a highly pigmented melanoma cell line with the patients' sera. Presence of IgG specific for the autoantigens in sera from patients with various panuveitis and healthy individuals was evaluated. Relation between the specific IgG and various clinicopathological features was examined. Results: KU-MEL-1 was found to be one of the 81 isolated positive clones representing 35 distinct genes, which is a previously isolated melanoma antigen preferentially expressed in melanocytes. The IgG Ab specific for KU-MEL-1 was detected in sera from patients with VKH in significantly higher amounts than in sera from patients with Behçet's disease, sarcoidosis, and from healthy individuals. Positive serum KU-MEL-1 Ab was significantly associated with HLA-DRB1*0405 and male VKH patients. Conclusion: KU-MEL-1 was identified as a new autoantigen for VKH. The highly frequent induction of IgG Ab for KU-MEL-1 in HLA-DRB1*0405 positive VKH patients may suggest the possible involvement of KU-MEL-1 specific CD4 + T cells in the pathogenesis of VKH, suggesting the possible use in the development of diagnostic and therapeutic treatments for VKH patients.